Can Cryptocurrencies Preserve Privacy and Comply With Regulations? - Goodell, Geoff; Aste, Tomaso (Frontiers in Blockchain, 2019)
Modern retail banking creates a kind of panopticon for consumer behaviour, ultimately promising to implement a mechanism that binds all of the financial activities undertaken by an individual to a single, unitary identity. In the age of Big Data, consumers have legitimate reasons to resist such surveillance, particularly in cases wherein monitoring is carried out without their knowledge and judgments based upon such monitoring are used to disincentivise or punish legitimate activities. The risk to consumers increases with the ever-increasing share of financial transactions that are performed electronically. Cryptocurrencies offer an alternative to traditional methods of electronic value exchange, promising anonymous, cash-like electronic transfers, but in practice they fall short for several key reasons. We consider the false choice between total surveillance, as represented by banking as currently implemented by institutions, and impenetrable lawlessness, as represented by privacy-enhancing cryptocurrencies as currently deployed. We identify a range of alternatives between those two extremes, and we consider two potential compromise approaches that offer both the auditability required for regulators and the anonymity required for users